2008
DOI: 10.1103/physrevlett.101.057006
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Induced Superconductivity inCaFe2As2

Abstract: CaFe2As2 has been found to be exceptionally sensitive to the application of hydrostatic pressure and can be tuned to reveal all the salient features associated with FeAs superconductivity without introducing any disorder. The ambient pressure, 170 K, structural/magnetic, first-order phase transition is suppressed to 128 K by 3.5 kbar. At 5.5 kbar a new transition is detected at 104 K, increasing to above 300 K by 19 kbar. A low temperature, superconducting dome (T(c) approximately 12 K) is centered around 5 kb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
671
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 615 publications
(717 citation statements)
references
References 6 publications
43
671
3
Order By: Relevance
“…Similar as in LaFeAsO [7,8], these ternary iron arsenides also exhibit a spin-density-wave-like anomaly and a structural transition from the tetragonal I4/mmm to the orthorhombic F mmm group at some temperature between 140 K and 200 K [9,10]. Furthermore, it was found that the high pressures can drive these undoped ternary iron arsenides superconducting [11][12][13].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar as in LaFeAsO [7,8], these ternary iron arsenides also exhibit a spin-density-wave-like anomaly and a structural transition from the tetragonal I4/mmm to the orthorhombic F mmm group at some temperature between 140 K and 200 K [9,10]. Furthermore, it was found that the high pressures can drive these undoped ternary iron arsenides superconducting [11][12][13].…”
Section: Introductionmentioning
confidence: 95%
“…Experimentally it was reported [11][12][13] that the ternary iron arsenides AFe 2 As 2 (A=Ba, Ca, or Sr) can become superconducting under high pressures without doping. This provides another route to study the salient features of these materials in connection with the intrinsic electronic structures and properties.…”
Section: E Pressure Effectmentioning
confidence: 99%
“…The application of modest pressure (a few kbars) was found to cause CaFe 2 As 2 to go superconducting [34]. Pressure dependent neutron diffraction measurements revealed a dramatic change in the crystal structure-a strongly first-order phase transition to a "collapsed" tetragonal phase [25,26].…”
Section: Cafe 2 As 2 Under Pressurementioning
confidence: 99%
“…By replacing La with other rare earths, T c can be raised to above 50 K [2][3][4][5][6][7]. Late on, the oxygen-free iron arsenide compounds AFe 2 As 2 (denoted as FeAs-122) were discovered and superconductivity was found by appropriate substitution or under pressure [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%